Do P-Wave Indices Manifest Atrial Fibrillation after Postoperative Atrial Fibrillation? - Rau, Christian; Salzmann-Djufri, Miriam; Böning, Andreas; Rohrbach, Susanne; Niemann, Bernd (The Thoracic and Cardiovascular Surgeon, 2025)
Postoperative atrial fibrillation (POAF) is a common complication following cardiac surgery. We investigated how POAF affects the manifestation of atrial fibrillation (AF) during long-term follow-up.We conducted a prospective all-comers investigation involving patients undergoing cardiac surgery. In propensity score-matched cohorts (POAF vs. sinus rhythm [SR]), ECGs were evaluated regarding P-wave duration (PWD), amplitude (PWA), morphology, variability, and their dynamics preoperatively pre-POAF and at follow-up. Predictive value of these parameters regarding the development of manifest AF after POAF was analyzed.Of 212 patients included, 50 patients (23.6%) developed POAF. Ninety patients underwent propensity score matching (PSM), 64 (71%) participated in follow-up, 21 (23%) died prior to follow-up (POAF: 13 vs. SR: 8), and 5 (6%) withdrew consent. No patient developed persistent AF. In nine patients, paroxysmal AF (pAF) events were detected (POAF: 6 vs. SR: 3). PWD, P-dispersion (PD), PWA, and interatrial block differed between POAF and SR. From pre- to postoperative ECGs, PD and P-wave peak time (PWPT) increased, and P-amplitude decreased in these. Preoperative β-blockers had only minor modulating potency. P-wave modulation was pronounced in POAF patients.Patients with POAF are prone to episodes of pAF. P-wave indices and perioperative dynamics of these indices may indicate a higher risk of manifest AF initiation among POAF patients.
Keywords: atrial fibrillation; outcomes (includes mortality, morbidity); surgery; complications